2012
DOI: 10.1063/1.3673258
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting on dielectric driven droplet resonance and mixing enhancement in parallel-plate configuration

Abstract: This study experimentally verifies that the mixing process in a droplet can be enhanced by driving the droplet at resonant frequencies and at alternating driving frequencies using a parallel-plate electrowetting on dielectric device. The mixing time, which is defined as the time required for reaching the well-mixed state, in a resonant droplet is found to be significantly shorter than that in a non-resonant droplet. Besides, it is also found that a higher driving potential leads to a better mixing effect, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In millimeter-sized systems, this flow is short lived, decaying within hundreds of microseconds, and the following dynamics are governed only by diffusion [23]. Previous studies of mixing driven by free-surface movement [24][25][26] have shown that free-surface dynamics can be effective in enhancing mixing within the enclosed liquid, even under conditions where molecular diffusion is negligible. However, the success of such chaotic advection-driven mixing or stirring relies on repeated stretching and folding of the "interface" between the two liquids being mixed.…”
Section: Introductionmentioning
confidence: 99%
“…In millimeter-sized systems, this flow is short lived, decaying within hundreds of microseconds, and the following dynamics are governed only by diffusion [23]. Previous studies of mixing driven by free-surface movement [24][25][26] have shown that free-surface dynamics can be effective in enhancing mixing within the enclosed liquid, even under conditions where molecular diffusion is negligible. However, the success of such chaotic advection-driven mixing or stirring relies on repeated stretching and folding of the "interface" between the two liquids being mixed.…”
Section: Introductionmentioning
confidence: 99%
“…This permits to induce shape oscillations of a sessile drop which in return generates a Stokes drift along its liquid surface. Subsequently, oscillating EWOD has been proposed as a mixing promoter in two popular configurations of electrowetting: the parallel-plate 7,8 and needle [9][10][11][12] configurations.…”
mentioning
confidence: 99%
“…In this regard, Paik et al have demonstrated droplet mixing using EWOD by fusing drops and then moving them back and forth on a linear array of electrodes [34]. Recently, Lee et al demonstrated mixing in electrowetting droplets in a sandwiched configuration by driving them at different resonant and at alternating driving frequencies [35].…”
Section: Discussionmentioning
confidence: 98%